A Feasibility study for the UP NEC/CEESG - Borjal, June U.; Manza, Pinky Maricris P.; Quintilla, Ma. Pilar D. (Diliman, Quezon City College of Engineering, 1995)
This study focused on the UP National Engineering Center Continuing Engineering Education Series Group (NEC/CEESG). CEESG specializes on the conduct of select short-term courses (e.g. Preventive Maintenance) as well as providing consultancy services. Analyses performed centered on the first area of specialization. The market analysis indicated that there was a problem regarding the CEESG's marketing strategy particularly promotion. Awareness of the CEESG's program among people in the industry was identified to be low (21% response rate from the targeted companies). Having identified the problem, the proponents of the study designed a scheme which would addressed it and eventually improve the market share to 2.4% from the current 0.31%. The succeeding analyses were based on this targeted market share. The technical analysis provided a comparison between the existing and the proposed scheme for the CEESG's operations. Cost estimates of fixed investment , operating cost and expenses, and start-up cost and expenses of the proposed scheme were determined. Total project cost amounted to P33,045,676. All values computed were based on the assumption that each course would be attended by the maximum number of participants (40 participants/seminar). The technical study revealed that the project was feasible. The financial analysis assessed the proposed scheme's commercial profitability as well as its capability to provide quality short-term courses that would continuously upgrade the Philippine industries. Income statements, cash flow projections and balance sheets for the years 1996-1998 were computed. The financial study also reaffirmed the project's feasibility. A social profitability analysis was also conducted to determine whereto the proposed scheme for the CEESG is socially attractive based on the benefits derived from it. The analysis covered the socio-economic conditions of the project to the following: *CEESG *UP NEC *UP CoE *UP System *Philippine Industry *Philippines. The social profitability analysis also showed the project's feasibility. All the analyses made proved that the project is indeed feasible. The study suggested areas for further study. An implementation plan for the completion of the project was also formulated.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: UP National Engineering Center; Vocational education; Participatory monitoring and evaluation (Project management)